2024
DOI: 10.3847/2041-8213/ad1e6c
|View full text |Cite
|
Sign up to set email alerts
|

The First Polarimetric View on Quasiperiodic Oscillations in a Black Hole X-Ray Binary

Qing-Chang Zhao,
Lian Tao,
Han-Cheng Li
et al.

Abstract: We present the first polarimetric analysis of quasiperiodic oscillations (QPOs) in a black hole binary utilizing IXPE data. Our study focuses on Swift J1727.8–1613, which experienced a massive outburst that was observed by various telescopes across different wavelengths. The IXPE observation we studied was conducted during the hard-intermediate state. The polarization degree (PD) and polarization angle (PA) were measured at 4.28% ± 0.20% and 1.°9 ± 1.°4, respectively. Remarkably, significant QPO signals were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Meanwhile, the hard X-ray flux measured by MAXI and Swift/BAT continues its descent. In Figure 2, we depict the HID of Swift J1727.8−1613, which aligns with the evolutionary trajectory obtained in previous studies (Nandi et al 2024;Peng et al 2024;Zhao et al 2024).…”
Section: Light Curves and Type C Qpos Of Swift J17278-1613supporting
confidence: 79%
See 2 more Smart Citations
“…Meanwhile, the hard X-ray flux measured by MAXI and Swift/BAT continues its descent. In Figure 2, we depict the HID of Swift J1727.8−1613, which aligns with the evolutionary trajectory obtained in previous studies (Nandi et al 2024;Peng et al 2024;Zhao et al 2024).…”
Section: Light Curves and Type C Qpos Of Swift J17278-1613supporting
confidence: 79%
“…The inconsistency in inclination estimates may arise from the L-T precession model not fully applying to Swift J1727.8-1613. Zhao et al (2024) conducted an analysis of the polarimetric data of this source and performed a phase-resolved analysis of the QPO using the Hilbert-Huang transform technique. The photon index displayed a significant modulation relative to the QPO phase.…”
Section: Qpo Rms and Phase Lagmentioning
confidence: 99%
See 1 more Smart Citation
“…As the outburst evolves, Svoboda et al (2024) found that the polarization degree decreases dramatically to 1% in the soft state, which suggested that the polarization is mainly contributed by the upscattered radiation in the hot corona. Meanwhile, based on a phase-resolved polarimetric analysis, Zhao et al (2024) found no modulations of polarization degree and polarization angle with the QPO phase in the 2-8 keV band for the same observation. This result poses a challenge to the hot flow precession model for Swift J1727.8-1613.…”
Section: Discussionmentioning
confidence: 79%
“…−16:12:19.23) was initially detected on 2023 August 24 (Kennea & Swift Team 2023;Negoro et al 2023), showing a remarkably intense outburst peaking at around 7Crab in the 2-20 keV energy range. A comprehensive evaluation of the source characteristics strongly supports its classification as a BHXRB from its X-ray spectrum (Liu et al 2023;Sunyaev et al 2023;Peng et al 2024), the identification of type C quasiperiodic oscillations (Bollemeijer et al 2023;Draghis et al 2023;Palmer & Parsotan 2023;Zhao et al 2024), and the detection of flat-spectrum radio emission indicative of a compact jet (Bright et al 2023;Miller-Jones et al 2023). The presence of the black hole in this X-ray binary is also suggested from the optical spectroscopy (Mata Sánchez et al 2024).…”
Section: Introductionmentioning
confidence: 95%